Komparasi Pendapat Ulama Madzhab Tentang Syirkah dan Prakteknya Dalam Pengembangan Bisnis UMKM - Nopianti, Nila; Munandar, Eris (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2025)
This article discusses the application of shirkah contracts, particularly shirkah al-mudharabah, in the development of Micro, Small and Medium Enterprises (MSMEs) in Indonesia. The background of this research focuses on the dominance of murabaha contracts in Islamic banking financing, which often do not meet the needs of businesses that want to avoid interest-bearing debt. This research uses descriptive and content analysis on the case of Toko Kurmanis to explore how cooperation between business owners and investors can improve access to capital and create a fair profit-sharing system. Through a literature review and content analysis of a video entitled “Kurmanis Business,” this research found that the implementation of shirkah not only provides financial benefits, but also promotes sustainable business growth. The main conclusion of this study shows that shirkah al-mudharabah can be an effective alternative in the development of MSMEs, with the potential to improve operational efficiency and expand market networks.